Inflation in African Countries : General Issues and Effecton the Financial Sector. (IMF Working Papers; Working Paper ;, 1989)
Since the mid-1970s the annual inflation rate in Africa has averaged more than 15 percent, with many countries experiencing rates of 20 percent or more. Inflation rates of this magnitude have significant adverse effects on the financial sectors of African countries, particularly in the context of fixed nominal interest rates. Econometric analysis points strongly to monetary expansion as a major cause of inflation in African countries generally. Exchange rate depreciation is also associated with higher inflation, although in some countries the domestic currency was depreciated to offset the effects of recent inflation, rather than being a cause of inflation.